Pengaruh Penerapan Model Problem Based Learning terhadap Hasil Belajar Pendidikan Pancasila Materi Gotong Royong di Kelas IV UPTD SDN Kamal 1 - Dina Maulida Yuniasari; Ana Naimatul Jannah (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
The aim of this research was to determine the effect of the problem based learning model on the learning outcomes of class IV students at UPTD SDN Kamal 1. The research design used was one group pre-test post-test. The sample in this research was all fourth grade students at SDN Kamal 1 consisting of 27 students. The sapling technique used in this research was saturated sapling. The data collections were using tests, observation and documentation. The influence between the application of the Problem Based Learning model and the learning outcomes of Pancasila education can be seen from the results of hypothesis testing. The results of the paired sample t-test that was carried out showed that the t value was 13.131 > 2.059, which means t count > t table, which means ho was rejected and hi was accepted. This means that there was an influence between the PBL model on the learning outcomes of class IV students at UPTD SDN Kamal 1.